(untitled) (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2024)
Human resource audit can help mitigate risk and create more value the certified lectures for universities by focusing on their strengths and weaknesses and improving their human resource processes. An emerging tool of human resource management to ensure certified lecture’s performance is very important, it will be long term human capital investment. Human resource audit actually a total quality control check on human resource activities in a University included certified lectures, and an assessment of how these activities support the strategy of the university to achieve the goals by certified lectures. Human resource audits studied in comparative approach, the auditors choose and use another certified lecture as the model that has sound and better practices. Human resource audit intents to motivate leaders instituting best suited diagnostic techniques of assessing performance of certified lectures against target and objectives established from the professionalism and experience of their own competencies. The excellence in this research is the high degree of performance measurement to evaluate the human capital investment. Comparative method is branded as best practices approach in which the auditors apply earlier research findings or the standards set by an outside (GAAS) as a benchmark is outside authority approach. In compliance approach, the auditors review early practices of the university to determine if those practices comply with legal requirements, strategies, policies, documentations and procedures of the university, and leader set objectives in their area of responsibility in Management by Objectives (MBO) approach.